2002
DOI: 10.1523/jneurosci.22-19-08458.2002
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Bcl-2-Associated Death Protein and Counter-Response of Akt within Cell Populations during Seizure-Induced Neuronal Death

Abstract: Bcl-2 family gene products are critical to the integration of cell death stimuli that target the mitochondrion. Proapoptotic BAD (Bcl-2-associated death protein) has been shown to dissociate from its sequestered site with the molecular chaperone protein 14-3-3 and displace proapoptotic BAX (Bcl-2-associated X protein) from antiapoptotic BCL-Xl. BAX subsequently translocates to the mitochondrion and induces cytochrome c release and caspase activation. Herein we report the response of the key members of this pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
171
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 174 publications
(194 citation statements)
references
References 58 publications
16
171
0
1
Order By: Relevance
“…This implies that the effects of wortmannin in vivo are reversible and do not result in neuronal cell death, at least in the amygdala. Similarly, LY294002 has been used in vivo in models of transient focal cerebral ischemia-or seizure-induced neuronal toxicity and, in these studies, LY294002 alone did not lead to increased neuronal cell death in the hippocampus or the caudate/putamen (40,41), presumably because of the surrounding glia. Our demonstration of transient PI3K inhibition by LY294002 in mixed neuronal/glial cultures provides strong support for the notion that metabolism, inactivation, or sequestration of LY294002 can have functional consequences for neuronal cell responses to a cell death-inducing stimulus.…”
Section: Discussionmentioning
confidence: 93%
“…This implies that the effects of wortmannin in vivo are reversible and do not result in neuronal cell death, at least in the amygdala. Similarly, LY294002 has been used in vivo in models of transient focal cerebral ischemia-or seizure-induced neuronal toxicity and, in these studies, LY294002 alone did not lead to increased neuronal cell death in the hippocampus or the caudate/putamen (40,41), presumably because of the surrounding glia. Our demonstration of transient PI3K inhibition by LY294002 in mixed neuronal/glial cultures provides strong support for the notion that metabolism, inactivation, or sequestration of LY294002 can have functional consequences for neuronal cell responses to a cell death-inducing stimulus.…”
Section: Discussionmentioning
confidence: 93%
“…Apoptosis may be triggered by two main pathways: activation of cell surfaceexpressed death receptors of the tumor necrosis factor TNF, superfamily and disruption to intracellular organelle homeostasis or DNA damage. 35) Seizure-induced mitochondrial dysfunction and activation of Bcl-2 family are calcium dependent or at least partly of calcium dependent, 38,39) whereas a role for death receptors contributing to seizure-induced neuronal death is less likely because there is no apparent requirement for calcium in the activation mechanism. 35,40) Our results suggest that the neuroprotective effect of PIP should be calcium dependent and participate in protecting intracellular organelles, such as mitochondrion and endoplasmic reticulum (ER).…”
Section: Discussionmentioning
confidence: 99%
“…In response to stress stimuli, Bax dissociates from 14-3-3 and translocates to mitochondria (30). In the event of seizure induced by kainate stimulation, Bax plays the same role in dissociation from 14-3-3, resulting in mitochondrial Bax accumulation after seizure (22). After translocation to mitochondria, Bax induces cytochrome c release either by forming a pore by oligomerization in the outer mitochondrial membrane or by opening other channels (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Regions-A previous study demonstrated mitochondrial Bax accumulation after seizure (22). To further elucidate the involvement of the mitochondrion-mediated apoptotic pathway induced by KA, the expression of Bax and cytochrome c in both mitochondria and the corresponding cytosol was examined by Western blotting.…”
Section: Tat-glur6-9c Attenuates Bax Translocation and The Release Ofmentioning
confidence: 99%